Strategi Mengurangi Sampah Plastik di Desa Citasuk - Dimas Bagaskara; Ulfa Fadliyah; Karin Seftiani; Linda Silvi Nursanti; Emiliana Putri; Bayu Budiman; Iqbal Salahudin Biki; Fajar Fauzi; Rizki Amilia; Mohamad Ikrom Arasid (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research shows that plastic bricks use plastic waste as a mixed material, offering an innovative solution in the construction sector that is more environmentally friendly and sustainable. The raw material used in making these bricks is plastic waste, which will reduce the amount of plastic waste thrown away in landfills. And the use of recycled plastic waste 5 (PP) polypropylene as a binding material in the paving block mixture produces maximum compressive strength.